Value-Action Gap in Climate Change Indonesians - Ardhi Arsala Rahmani; Muhammad Ery Wijaya; Fajar B. Hirawan (Jurnal Wilayah dan Lingkungan, 2021)
The problem of climate change is defined by continued sea-level rise, melting of the ice caps, and increasing global temperatures. However, despite increasing informational awareness towards these facts by government and grassroots advocacy in many countries, emissions as the leading determinant of climate change continue to rise, with the growing consumption and activities being major emitters. In behavioral studies, this gap between perceived concerns and reflected actions is called the ‘value-action gap’ (VAG). This research evaluates the existence of a VAG among the Indonesians as increasingly significant emitters. Therefore, this researchaims to determines whether relationships exist between climate change knowledge, reported concerns, and exhibited actions taken to mitigate climate change. The research proposes the hypotheses that concerns and awareness of climate change are high among the studied population, but do not influence high climate behavior. The research gathers three class variables through a quantitative sampling, namely climate change knowledge, climate change concerns, and climate change behaviors. The gap is then calculated as a subtraction score between the latter two variables. Moreover, discrepancies between the actions taken and reported concerns are assessed, showcasing policy implications going forward.The findings of this research based on the sample suggest that varying income groups of urbanite households hold significant knowledge of climate change and have reported concerns towards the issue, and that the two as variables are linked to each other.